Vpu of a Simian Immunodeficiency Virus Isolated from Greater Spot-Nosed Monkey Antagonizes Human BST-2 via Two AxxxxxxxW Motifs - Yao, Weitong (J Virol, 2020)
BST-2/CD317/tetherin is a host transmembrane protein that potently inhibits human immunodeficiency virus type 1 (HIV-1) virion release by tethering the nascent virions to the plasma membrane. Viral protein U (Vpu) is an accessory protein encoded by HIV-1 as well as by some simian immunodeficiency viruses (SIVs) infecting wild chimpanzees, gorillas, or monkeys (SIVcpz, SIVgor, or SIVgsn/SIVmon/SIVmus, respectively). HIV-1 Vpu directly binds to and downregulates human BST-2. The antagonism is highly species specific because the amino acid sequences of BST-2 are different among animal species. Here, we show that Vpu proteins from several SIVcpz, SIVgsn, SIVmon, or SIVmus isolates fail to antagonize human BST-2. Only Vpu from an SIVgsn isolate (SIVgsn-99CM71 [SIVgsn71]) was able to antagonize human BST-2 as well as BST-2 of its natural host, greater spot-nosed monkey (GSN). This SIVgsn Vpu interacted with human BST-2, downregulated cell surface human BST-2 expression, and facilitated HIV-1 virion release in the presence of human BST-2. While the unique (14)AxxxxxxxW(22) motif in the transmembrane domain of HIV-1(NL4-3)Vpu was reported to be important for antagonizing human BST-2, we show here that two AxxxxxxxW motifs (A(22)W(30) and A(25)W(33)) exist in SIVgsn71 Vpu. Only the A(22)W(30) motif was needed for SIVgsn71 Vpu to antagonize GSN BST-2, suggesting that the mechanism of this antagonism resembles that of HIV-1(NL4-3) Vpu against human BST-2. Interestingly, SIVgsn71 Vpu requires two AxxxxxxxW (A(22)W(30) and A(25)W(33)) motifs to antagonize human BST-2, suggesting an as-yet-undefined way that SIVgsn71 Vpu works against human BST-2. These results imply an evolutionary impact of primate BST-2 on lentiviral Vpu. IMPORTANCE Genetic alterations conferring a selective advantage in protecting from life-threating pathogens are maintained during evolution. In fact, the amino acid sequences of BST-2 differ among primate animals and their susceptibility to viral proteins is species specific, suggesting that such genetic diversity has arisen through the evolutionarily controlled balance between the host and pathogens. The M (main) group of HIV-1 is thought to be derived from SIVcpz, which utilizes Nef, but not Vpu, to antagonize chimpanzee BST-2. SIVcpz Nef is, however, unable to antagonize human BST-2, and Vpu was consequently chosen again as an antagonist against human BST-2 in the context of HIV-1. Studies on how Vpu lost and acquired this ability, together with the distinct mechanisms by which SIVgsn71 Vpu binds to and downregulates human or GSN BST-2, may help to explain the evolution of this lentiviral protein as a result of host-pathogen interactions.